PERANCANGAN APLIKASI INVENTORI BARANG BERBASIS WEB PADA BENGKEL HYDRAULIC STEERING GEAR - Fernando, Liko; Tony (Jurnal Serina Abdimas, 2025)
Hydraulic Steering Gear Workshop is a workshop that offers spare parts, repair services to the process of installing ship spare parts, there are several problems that occur in the workshop including lack of stock, errors in recording goods, to duplication of data in the process of documentation of incoming and outgoing goods. Based on the existing problems, this study was conducted to develop a web-based Inventory Application that aims to make time more effective in searching for incoming and outgoing goods data, and to avoid duplication of goods data in the warehouse. The design of the Inventory Application uses a software development methodology, namely Scrum, and the php programming language with a MySQL Database. The results of this study are a web-based Inventory Application that can help workshop owners in searching for and organizing goods in the workshop warehouse ABSTRAK Bengkel Hydraulic Steering Gear adalah bengkel yang menawarkan suku cadang, jasa perbaikan hingga proses pemasangan suku cadang kapal, terdapat berberapa masalah yang berlangsung dalam bengkel diantaranya kekurangan stok, kekeliruan dalam pendataan barang, hingga duplikasi data dalam proses dokumentasi barang yang masuk dan keluar. Berdasarkan permasalahan yang ada maka penelitian ini dilaksanakan untuk mengembangkan Aplikasi Inventori berbasis web yang bertujuan untuk mengefektifkan waktu dalam mencari pendataan barang yang masuk dan keluar, serta menghindari terjadinya duplikasi sebuah data barang dalam gudang. Perancangan Aplikasi Inventory menggunakan metodologi pengembangan perangkat lunak yaitu Scrum, dan bahasa pemograman PHP dengan database MySQL. Hasil dari penelitian ini adalah Aplikasi Inventori berbasis web yang dapat membantu pemilik bengkel dalam mencari dan menata barang yang ada di dalam gudang bengkel.